A Multi-Institutional Study Comparing the Use of the American Joint Committee on Cancer 7th Edition Esophageal versus Gastric Staging System for Gastroesophageal Junction Cancer in a Western Population. Issue 1 (January 2017) - Adeshuko, Folashade A.; Squires, Malcolm H.; Poultsides, George; Pawlik, Timothy M.; Weber, Sharon M.; Schmidt, Carl; Votanopoulos, Konstantinos; Fields, Ryan C.; Maithel, Shishir K.; Cardona, Kenneth
Controversy exists over the staging of gastroesophageal junction (GEJ) adenocarcinomas. The aim of our study was to assess the adequacy of the American Joint Committee on Cancer 7th edition esophageal (E7) and gastric (G7) staging systems for GEJ tumors in a western population. All patients with GEJ adenocarcinoma who underwent curative resection from 2000 to 2012 were identified from the United States Gastric Cancer Collaborative database and assessed according to the E7 and G7 systems. Fifty-one patients were identified. Neither the E7 nor G7 system adequately stratified patients by Tor N stage with a loss of distinctiveness between T1 to 4 and N0 to 3 tumors. On final stage analysis, the outcomes were similar between both systems; however, neither system, with the exception of the G7 stage I versus II, adequately stratified patients by stage (E7: I vs II, P = 0.07; II vs III, P = 0.23; G7: I vs II, P = 0.02; II vs III, P = 0.13). Histologic grade was not associated with survival (P = 0.27) and did not improve the ability to stratify patients in the E7 system. Our study identifies limitations in the proper stratification of patients with GEJ adenocarcinoma using either the American Joint Committee on Cancer 7th esophageal or gastric systems. The classification of GEJ adenocarcinoma within either system needs to be further studied in a larger patient population.